Studi Analisis Penurunan Tanah Lempung Lunak dan Tanah Lempung Organik Menggunakan Pemodelan Matras Beton Bambu - Nawawi, Nawawi; Afriani, Lusmeilia; Iswan, Iswan (Universitas Lampung, 2017)
The strength of infrastructure buildings is influenced by the type of soil underneath. One type of land that is widely found in the land in the province of Lampung is fine-grained soil. The fine grained soil is meant soft clay and organic clay. Construction of the above clay will experience significant land subsidence constraints when given the loading. The load that causes the pore water pressure increases so that the pore water out and soil decreases consolidatively. Therefore, it is necessary to study soil degradation using box test and bamboo concrete mats as a means of land degradation. The result of clay decline testing using boks modeling and bamboo concrete mat, soft clay experience faster rate of process of decline (Cv) than organic clay. The magnitude of soft clay (Cc) decline is less than that of organic clay. Soft clay volumes are also changing volume (Mv) faster than organic clay. Coeficient of compression(av) of soft clay is also faster than organic clay. The total decline in total soil over a 20 year period on soft clay is smaller than that of organic clay. Keywords : Clay, Test Box, Bamboo Concrete Mattress, Soil Consolidation